A Study of Secondary School Students’ and Teachers’ Perceptions of and Satisfaction with Service Learning Activities at Ruamrudee International School in Thailand - Vu, Tin (Scholar: Human Sciences, 2014)
This study was conducted mainly to examine a service-learning program at RIS by determining students’ and teachers’ perception of the linkage and satisfaction with service learning activities and classroom learning experiences done at RIS. The sample included 254 secondary students and 52 teachers from Ruamrudee International School. This research found differences in students’ and teachers’ perceptions of service learning activities and satisfaction of learning experience statistically significant. Teachers gave a high rating to perceptions and satisfaction than students. A number of suggestions were given by students showing how important that service learning has been in strengthening and enhancing their education. Service Learning has served to enhance the process of making connections with learning in classroom and bringing to life through the experiences of serving and learning. In conclusion, the researcher suggests when constructing service learning activities, consider the needs of students, and elicit the support of teachers and the community partners. It is crucial to have the whole community join force and working together to bring out what is best for all.